2009
DOI: 10.1007/s00240-009-0234-0
|View full text |Cite
|
Sign up to set email alerts
|

Urinary obstruction depresses erythropoiesis which recovers after parenchyma-saving surgery but not SWL

Abstract: We tested the hypotheses that chronic human urinary obstruction impairs the renal regulation of the red blood cell (RBC) production and compared the chronic outcome of relief of obstruction between parenchyma-saving surgery and extracorporeal lithotripsy (SWL). We measured RBC count and serum erythropoietin (Epo) concentration before and 3 months after relief of urinary obstruction in 60 patients treated with pyelolithotomy, ureterolithotomy or ureteroscopy and in 62 patients treated with SWL. Compared with 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…4,25 A study showed that obstructive uropathy was associated with clinically relevant effects on erythropoiesis in human patients. 26 Moreover, anaemia seems to be common after ureteral surgery due to haemorrhage during the procedure, erythropoietin production defect after kidney injury due to ongoing CKD and prolonged obstruction or surgical procedures. 25,27 Finally, fluid resuscitation is also associated with hospital-acquired anaemia, and institution of fluid therapy lowers PCV.…”
Section: Discussionmentioning
confidence: 99%
“…4,25 A study showed that obstructive uropathy was associated with clinically relevant effects on erythropoiesis in human patients. 26 Moreover, anaemia seems to be common after ureteral surgery due to haemorrhage during the procedure, erythropoietin production defect after kidney injury due to ongoing CKD and prolonged obstruction or surgical procedures. 25,27 Finally, fluid resuscitation is also associated with hospital-acquired anaemia, and institution of fluid therapy lowers PCV.…”
Section: Discussionmentioning
confidence: 99%
“…Eterović et al showed that ESWL caused a transient increase in EPO levels independent of hemoglobin levels. This increase is attributed to intrarenal microcirculatory disorders resulting in tissue hypoxia (25). In an animal study on pigs, Willis et al established 3 groups: ESWL only (Group 1); ESWL after verapamil (Group 2); and sham (Group 3).…”
Section: Discussionmentioning
confidence: 99%